Effects of combining contingency management with behavioral activation for smokers with depression. (4th March 2019) - González-Roz, Alba; Secades-Villa, Roberto; Alonso-Pérez, Fernando
Abstract: Background: Few studies on Behavioral Activation (BA) have been conducted among smokers with depression and very scarce evidence on Contingency Management (CM) in this population exists. This study aimed to examine the effectiveness of cognitive behavioral treatment (CBT) plus BA and the same treatment alongside CM on smoking abstinence and depression at the end of treatment. Method: A sample of 74 treatment-seeking smokers (78.4% female) were randomly assigned to two treatment conditions delivered in 90-minute sessions over 8 weeks: CBT + BA ( n = 41), or CBT + BA + CM ( n = 33). Depression was assessed through clinical interviews and using the Beck Depression Inventory-II. Smoking abstinence was verified through both carbon monoxide and urinalyses. Results: A greater percentage of patients receiving CBT + BA + CM attended all treatment sessions than those in CBT + BA (93.5% vs 71.1%). Among the total sample, 67.6% gave up smoking at the end of treatment. Abstinence rates were equivalent for CBT + BA and CBT + BA + CM at post-treatment (63% vs 72.7%). Participants showed a statistically significant improvement in depressive symptoms with no differences across treatments (CBT + BA: Mdn = 11, IQR = 5, 15 vs CBT + BA + CM: Mdn = 10, IQR = 5, 14). Conclusions: Findings support and expand previous evidence by showing that smokers with depression achieve high cessation rates without suffering negative mood changes. These results also offer a novel contribution by suggesting that BA and CM are promising interventions for this difficult to treat population. Additionally, research exploring long-term effects of both treatments is warranted.